The banking degree 1969 (1969)
the banking of 1969, which contains issues relating to licensing of banks, duties of licensed banks, powers of the central bank and other related matters.
Supplement to official gazette extraordinary no.8, vol.56, 11th February 1969 part A.
nmn, 27/03/19
Loans
Keywords: Banks and banking; Banking decree; Nigeria